Pengaruh Penanaman Modal Asing Terhadap Produk Domestik Bruto Indonesia Tahun 2009-2022: (PDB) - Ardini, Cheva Adisty; Fisabilillah, Ladi Wajuba Perdini (Universitas Negeri Surabaya, 2024)
This study was conducted with the aim of determining the influence of Foreign Investment on Gross Domestic Product in Indonesia in 2009-2022. The type of research used in this study is a quantitative approach. The data used is secondary time series data from 2009-2022 sourced from the official website of the Central Statistics Agency and the World Bank. The data analysis technique uses simple linear regression with the help of the Eviews-12 analysis tool. The results of this study show that foreign investment has effect on Indonesia's gross domestic product in 2009-2022. This discovery can be interpreted as an indication that the magnitude of foreign investment flows affects the country's economic development, which is reflected in the size of the gross domestic product.